The contribute of cerebrospinal fluid free light-chain assay in the diagnosis of multiple sclerosis and other neurological diseases in an Italian multicenter study. (August 2022) - Bernardi, Gaetano; Biagioli, Tiziana; Malpassi, Paola; De Michele, Teresa; Vecchio, Domizia; Repice, Anna Maria; Lugaresi, Alessandra; Mirabella, Massimiliano; Torri Clerici, Valentina; Crespi, Ilaria
Background: Cerebrospinal fluid (CSF) free light chains (FLCs) can be an alternative assay to oligoclonal bands (OCBs) in inflammatory neurological disorders, but threshold has no consensus. Objective: To assess the diagnostic accuracy of CSF FLCs in multiple sclerosis (MS) and other neurological diseases. Methods: A total of 406 patients from five Italian centers. FLCs were measured in CSF and serum using Freelite MX assays on Optilite. Results: A total of 171 patients were diagnosed as MS, 154 non-inflammatory neurological diseases, 48 inflammatory central nervous system (CNS) diseases, and 33 peripheral neurological diseases. Both kFLC and λFLC indices were significantly higher in patients with MS compared to other groups ( p < 0.0001). The kFLC index ⩾ 6.4 is comparable to OCB for MS diagnosis (area under the receiver operating characteristic curve (AUC) = 0.876; sensitivity 83.6% vs 84.2%; specificity 88.5% vs 90.6%). λFLC index ⩾ 5 showed an AUC of 0.616, sensitivity of 33.3% and specificity of 90.6%. In all, 12/27 (44.4%) MS patients with negative OCB had kFLC index ⩾ 6.4. Interestingly, 37.5% of 24 patients with a single CSF IgG band showed high kFLC index and 12.5% positive λFLC index. Conclusion: Our findings support the diagnostic utility of FLC indices in MS and other CNS inflammatory disorders, suggesting a combined use of FLC and OCB to help clinicians with complementary information.